2021
DOI: 10.1111/1467-8462.12414
|View full text |Cite
|
Sign up to set email alerts
|

Economic Aspects of Loneliness in Australia

Abstract: We highlight the problem of loneliness, and argue that it is not only a public health issue but also an economic problem. We provide a brief review of findings from the key literature on the associations between loneliness, mental and physical health, and healthcare costs; and then present some evidence on its trends, the extent of socioeconomic inequalities and its links with health and healthcare usage, in Australia. We hope to encourage further economics research on loneliness, and related issues of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 69 publications
(84 reference statements)
3
27
0
Order By: Relevance
“…The raw correlations between the three social health measures at baseline are: lonely/social isolation = 0.080 for men, 0.065 for women; lonely/lack of social support = 0.173, 0.156; and social isolation/lack of social support = 0.112, 0.097). This is consistent with previous studies that have found that these correlations are modest (Kung et al 2021;Newall and Menec 2017). However, in our panel transitional model we explicitly allow for loneliness, social isolation and a lack of social support to be jointly determined (i.e.…”
Section: Measuring Social Health: Loneliness Social Isolation and Social Supportsupporting
confidence: 85%
See 4 more Smart Citations
“…The raw correlations between the three social health measures at baseline are: lonely/social isolation = 0.080 for men, 0.065 for women; lonely/lack of social support = 0.173, 0.156; and social isolation/lack of social support = 0.112, 0.097). This is consistent with previous studies that have found that these correlations are modest (Kung et al 2021;Newall and Menec 2017). However, in our panel transitional model we explicitly allow for loneliness, social isolation and a lack of social support to be jointly determined (i.e.…”
Section: Measuring Social Health: Loneliness Social Isolation and Social Supportsupporting
confidence: 85%
“…Loneliness is also strongly associated with suicidal ideation and suicidal attempts, even after accounting for common mental disorders (Stickley and Koyanagi 2016). Consequently, there are substantive costs of loneliness to healthcare systems (Kung et al 2021;Mihalopoulos et al 2020). Loneliness is therefore becoming increasingly recognised as a major public health, demographic and economic issue that needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations